Four Tier-Relativity Diagnostic Test (4T-RDT) to Identify Student Misconception - Irnin Agustina Dwi Astuti; Yoga Budi Bhakti; Rendi Prasetya; Yulika Rahmawati (STKIP Singkawang, 2023)
Misconceptions in physics lessons are still the main problem faced by teachers and students. Misconceptions of physics occur at various levels of education and many physics materials at the high school level. The results of observation to class XII students in Semarang obtained data that the material on the theory of relativity is material with a low level of mastery of concepts. In addition, teachers also have difficulty in identifying physical misconceptions experienced by students. Therefore, this study aims to develop an instrument in the form of a Four-Tier Diagnostics Test to identify students' physics misconceptions on the material of relativity theory, determine the level of validity, reliability, and characteristics of the four-tier diagnostics test. The type of research is Research and Development (R&D). The methods used are documentation, interviews, questionnaires and tests. The results showed that the instruments were valid and reliable. The diagnostic test consists of four levels, namely: a question with one answer key and four distractor, the degree of confidence of the answer, the reason, and the level of confidence of the reason. The resulting instrument consists of a grid, work instructions, test questions, answer keys, answer sheets, scoring guidelines, and result interpretation guidelines. Validity testing by expert validators shows the developed instrument is valid and reliable.